2021
DOI: 10.1016/j.bbi.2021.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the cellular specificity of TSPO imaging in a rat model of peripherally-induced neuroinflammation

Abstract: Highlights [ 18 F]DPA-714 PET showed an increased brain signal following peripheral LPS challenge. The cellular origin of TSPO signal appears to depend on the brain region examined. TSPO signal increase in the hippocampus arises from microglia and astrocytes. Microglia, macrophages and astrocytes are the main contributors in the substantia nigra. Macrophages and microglial cells expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…Our data show that peripherally-induced neuroinflammation can be reliably detected in the CNS using the TSPO-PET radioactive tracer [18F] DPA-714. Our results supported the conclusion that the resulting increase in [18F] DPA-714 TSPO signaling is primarily attributable to a combination of microglia, astrocytes, and monocyte-derived macrophages [ 33 ]. This study focused on the expression of the DPA-714 signal in glial cells.…”
Section: Discussionsupporting
confidence: 88%
“…Our data show that peripherally-induced neuroinflammation can be reliably detected in the CNS using the TSPO-PET radioactive tracer [18F] DPA-714. Our results supported the conclusion that the resulting increase in [18F] DPA-714 TSPO signaling is primarily attributable to a combination of microglia, astrocytes, and monocyte-derived macrophages [ 33 ]. This study focused on the expression of the DPA-714 signal in glial cells.…”
Section: Discussionsupporting
confidence: 88%
“…TSPO signal in the hippocampus reportedly arises from microglia and astrocytes, whereas microglia, macrophages and astrocytes are the main contributors in the substantia nigra. 59 In this work, evaluation was exclusive to the frontal cortex which may have characteristically unique TSPO cellular origin. These immunostaining studies show that it is imperative to investigate TSPO expression in human tissue acquired from diseased patients compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…TSPO expression has been reportedly regulated by a variety of factors including immune cell activation state, neuronal activity and ROIs studied. 55 , 59 , 63 The inconsistencies with TSPO expression between neuroinflammatory conditions contribute to the need for additional neuroinflammation imaging targets with higher specificity than TSPO towards CTE.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the use of TSPO PET imaging techniques to measure brain inflammation is that it is unclear what cell type is responsible for the TSPO binding signal. For many years, TSPO was thought to be specific to microglial activation, yet TSPO can also be bound by other inflammatory cells, including astrocytes and peripheral immune cells 73-76 . More recent studies in rodent models have suggested that TSPO signal may be related more to microglial number than microglial activation 77 .…”
Section: Discussionmentioning
confidence: 99%